1994
DOI: 10.1111/j.1539-6924.1994.tb00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia Risk Associated with Benzene Exposure in the Pliofilm Cohort. II. Risk Estimates

Abstract: The detailed work histories of the individual workers composing the Pliofilm cohort represent a unique resource for estimating the dose-response for leukemia that may follow occupational exposure to benzene. In this paper, we report the results of analyzing the updated Pliofilm cohort using the proportional hazards model, a more sophisticated technique that uses more of the available exposure data than the conditional logistic model used by Rinsky et al. The more rigorously defined exposure estimates derived b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…The algorithm included the application method (tractor-or boom-, backpack-, bike-spraying), the method of mixing and loading (direct tank filling, pouring, or scooping), the method of bulb disinfection (manual or mechanical dipping), the application rate (milligrams per hectare), the bulb acreage (hectares), the number of applications, the number of bulbs disinfected per year (number of containers), and a protection factor for personal protective equipment (range: 0 = no protection to 1 = complete protection) (24). In a study of Pliofilm™ workers, exposure to benzene was calculated on the basis of the concentration of benzene in the cement being used, the number of skin contacts with the cement per day, the surface area of the contacted skin (square centimeters), and the contact time (hours per day) (25)(26)(27). Dermal uptake (milligrams per kilogram per day) was subsequently calculated using these dermal exposure estimates, the dermal absorption rate (milligram per square centimeter per hour), and body weight of the individual (kilograms).…”
Section: Quantitative Estimatesmentioning
confidence: 99%
“…The algorithm included the application method (tractor-or boom-, backpack-, bike-spraying), the method of mixing and loading (direct tank filling, pouring, or scooping), the method of bulb disinfection (manual or mechanical dipping), the application rate (milligrams per hectare), the bulb acreage (hectares), the number of applications, the number of bulbs disinfected per year (number of containers), and a protection factor for personal protective equipment (range: 0 = no protection to 1 = complete protection) (24). In a study of Pliofilm™ workers, exposure to benzene was calculated on the basis of the concentration of benzene in the cement being used, the number of skin contacts with the cement per day, the surface area of the contacted skin (square centimeters), and the contact time (hours per day) (25)(26)(27). Dermal uptake (milligrams per kilogram per day) was subsequently calculated using these dermal exposure estimates, the dermal absorption rate (milligram per square centimeter per hour), and body weight of the individual (kilograms).…”
Section: Quantitative Estimatesmentioning
confidence: 99%
“…8, 11 We can estimate that our workers will be exposed to less than 50 ppm-years until retirement, which has not been demonstrated to increase the risk of developing acute myeloid leukemia, 12 and it has been estimated that the lifetime risk of acute leukemia with such exposures is not significantly higher than the risk in the general population. 13 Myeloproliferative diseases are uncommon in the general population and in workers exposed to low concentrations of benzene at work. Therefore, a finding of independent progenitor cell colony growth in a worker exposed to benzene should not be used as evidence of an increased risk for disease and not in decisions of fitness for work.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that exposure to benzene may be associated with other leukemias, such as chronic myeloid leukemia and multiple myeloma (NIOSH, 1977;Rinsky et al, 1981Rinsky et al, , 1987Snyder, 2000). However, failure to identify additional cases of multiple myeloma in the Pliofilm cohort weakens any previously reported associations between multiple myeloma and benzene exposure (Paxton et al, 1994a(Paxton et al, , 1994bPaxton, 1996;Wong, 1995). No association between leukemogenic effects and low or background concentrations of benzene (less than 0.5 ppm) has been shown (Raabe & Wong, 1996).…”
mentioning
confidence: 89%